1986
DOI: 10.1063/1.451767
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of H2O2 photodissociation: OH product state and momentum distribution characterized by sub-Doppler and polarization spectroscopy

Abstract: Hydrogen peroxide has been optically excited at a wavelength of 266 nm and the OH photofragment completely characterized by Doppler and polarization spectroscopy using the laser-induced fluorescence technique. The entire internal state distribution (vibration, rotation, spin, and A components), translational energy, angular distribution, rotational alignment, and vector correlations between rotational and translation motions of OH products is measured. The hydroxyl radicals are formed in the X 211 3/2 ,112 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(95 citation statements)
references
References 57 publications
7
88
0
Order By: Relevance
“…This phenomenon can be explained by formation of hydrogen bonds between free silanol groups and hydrogen peroxide. In the experimental conditions, almost all of silanol groups were ionized as mesoporous silanol groups existed in two forms, Si-(OH) 2 and Si-(OH) with pK a values, respectively, 8.2 and 2.0 [49]. …”
Section: Hydrogen Peroxide Adsorption Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon can be explained by formation of hydrogen bonds between free silanol groups and hydrogen peroxide. In the experimental conditions, almost all of silanol groups were ionized as mesoporous silanol groups existed in two forms, Si-(OH) 2 and Si-(OH) with pK a values, respectively, 8.2 and 2.0 [49]. …”
Section: Hydrogen Peroxide Adsorption Analysismentioning
confidence: 99%
“…Hydrogen peroxide is a very useful oxidizer that has been employed in many different fields, such as chemistry of atmosphere [1], autodissociation dynamics [2,3], and bleaching [4]. It is reasonably stable, readily available, inexpensive, and generates only water as a by-product [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, H 2 CO is known to dissociate mainly to CO(V)0), so from Doppler profiles of the H 2 fragment one could determine the correlation between H 2 (V,J) levels and average CO (V)0) rotational excitation, demonstrating that the latter decreases with increasing vibrational excitation of the H 2 . 32 While the energy resolution provided by Doppler spectroscopy is somewhat limited, the real power of Doppler/LIF measurements was demonstrated in a series of experimental [72][73][74][75] and theoretical 76 papers published in 1986. These studies showed that the shapes of Doppler profiles are sensitive to the photofragment alignment.…”
Section: The Development Of Experimental Tools In Photodissociatimentioning
confidence: 99%
“…Given the considerable usefulness of hydrogen peroxide in many fields, such as atmospheric chemistry, 1 photodissociation dynamics, [2][3][4][5][6] and oxidation reactions, 7 and of urea in biological processes because of potential hydrogen-bonding and acidbase properties associated with both the amine and the carbonyl groups, the ureashydrogen peroxide (UHP) 1:1 complex has been widely used in several oxidation processes [8][9][10][11][12] and also as a safe source to produce hydrogen peroxide. 13 The crystal structure of UHP 1:1 complex was first experimentally investigated by X-ray 14 and later by neutron diffraction at low temperatures.…”
Section: Introductionmentioning
confidence: 99%